Coupling coordination and sustainability among water resource carrying capacity, urbanization, and economic development based on the integrated model - Zhang, Qianrong; Bee, Hazirah; Wang, Yao; He, Junjie (Frontiers in Environmental Science, 2025)
Introduction: The coupling coordination development among Water Resources Carrying Capacity (WRCC), Urbanization Level (UL), and Economic Development Level (EDL) is a critical indicator for regional socio-economic and ecological sustainability. Although existing studies on WRCC and coupling coordination are abundant, in-depth study on the evolution law of coupling coordination and its influence mechanism are still lacking.Methods: This study proposes an innovative integrated model combining the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS), coupling coordination degree (CCD) analysis, and nonlinear polynomial regression, to dynamically assess the interplay among WRCC, UL, and EDL in Sichuan Province, China from 2010 to 2019. Key innovations include: First, a hybrid weighting method to balance objectivity and expert knowledge in evaluating WRCC, UL, and EDL, integrating entropy and Analytic Hierarchy Process (AHP). Second, a dynamic CCD model capturing multi-system synergies and a nonlinear regression framework quantifying interaction effects.Results and Discussion: WRCC exhibited a wavy upward trend, peaking at 0.60 in 2018 and 2019, with spatial characteristics of “strong in the west, weak in the east, and stable in the center.” CCD shows a trend of lagging coordination, from basic coordination (0.4–0.5 in 2010–2014) to full coordination (0.6–0.8 in 2018–2019), with 18 cities surpassing 0.6. Regression analysis revealed that CCD is predominantly driven by interactions between systems, R2 is 0.973, where WRCC-EDL synergy exerted the strongest influence, coefficient is 0.780. This model provides a scientific foundation for optimizing water resource management and fostering sustainable urbanization-economy-resource synergies in ecologically fragile yet rapidly developing regions.